THE ROLE OF @bts.bighitofficial INSTAGRAM REELS CONTENT IN SHAPING ARMY FAN LOYALTY IN EAST JAKARTA - Rini Wulandari; RR. Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The development of social media has transformed the pattern of communication between public figures and their fans. One of the most widely used features is Instagram Reels, which enables the delivery of information, entertainment, and interaction in a fast and engaging manner. This study aims to examine the role of Instagram Reels content on @bts.bighitofficial in shaping the loyalty of ARMY fans in East Jakarta. The study employs the Uses and Gratifications Theory, which views audiences as active users who utilize media to fulfill their needs for information, entertainment, social interaction, and personal identity. A descriptive qualitative approach was used, with informants selected through purposive sampling. Data were collected through in-depth interviews, observation, documentation, and data triangulation. The informants consisted of three ARMY fans in East Jakarta who actively followed Reels content from the @bts.bighitofficial account. The findings reveal that BTS Reels content is characterized by informational, entertaining, and interactive content that fulfills fans’ needs. The study also found a high level of fan loyalty, demonstrated through active engagement in digital activities, support for BTS’s works, participation in fandom communities, and strong emotional attachment. Therefore, Instagram Reels content on @bts.bighitofficial plays a significant role in fulfilling fans’ needs and contributes to the development and maintenance of ARMY fan loyalty in East Jakarta.